Plasma palmitoylethanolamide (PEA) as a potential biomarker for impaired coronary function. (15th March 2017) - Quercioli, Alessandra; Carbone, Federico; Bonaventura, Aldo; Liberale, Luca; Pataky, Zoltan; Thomas, Aurélien; Lenglet, Sébastien; Lauer, Estelle; Golay, Alain; Dallegri, Franco; Di Marzo, Vincenzo; Schindler, Thomas H.; et al.
Abstract: Background: Among endocannabinoid (EC)-related mediators, Oleoyl-ethanolamide (OEA) and Palmitoyl-ethanolamide (PEA), two endogenous PPARα agonists with lipolytic and anti-inflammatory action, respectively, are being actively investigated. Here, we assessed the potential association between plasma levels of PEA and OEA and coronary function in a cohort including normal, overweight, obese, and morbidly obese (MOB) individuals. Methods: Myocardial perfusion and endothelium-related myocardial blood flow (MBF) responses to cold pressor test (CPT) and during pharmacological vasodilation with dipyridamole were measured with 13 N-ammonia positron emission tomography/computed tomography. OEA and PEA were extracted from human plasma by liquid-liquid extraction, separated by liquid chromatography and quantified by mass spectrometry. Serum levels of intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 (VCAM-1) were measured by colorimetric enzyme-linked immunosorbent assay. Results: Circulating levels of PEA and VCAM-1 were increased in MOB as compared to normal weight subjects. Circulating levels of OEA and PEA were associated with body mass index, but not with adhesion molecules. Increases of PEA levels were associated with and predictive of worsened coronary function in MOB and the overall cohort studied. Conclusion: Plasma levels of PEA are increased in MOB patients and associated with coronary dysfunction as a functional precursor of CAD process. Larger trials are needed to confirm PEA as a potential circulating biomarker of coronary dysfunction in both MOB patients and the general population.